Studying international spillovers in a New Keynesian continuous time framework with financial markets - Bernd Hayo; Britta Niehof (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
In light of the recent financial and real economic crisis, it seems clear that macroeconomists need to better account for the influence of financial markets. This paper explores the consequences of treating the interaction between different financial markets, monetary policy, and the real economy seriously by developing a fully dynamic theoretical model. Starting from a standard New Keynesian framework, we reformulate and extend the model by means of stochastic differential equations so as to analyse spillover effects and steady-state properties. We solve the model for theoretically derived parameters, distinguishing between (almost) closed, equally sized, and differently sized economies. Applying Bayesian estimation methods, we estimate model parameters for Canada and the United States. Using Lyapunov techniques, we find evidence of instability in the US and Canadian financial systems.
Keywords: C02; C63; E44; E47; E52; F41; 330; New Keynesian Model; Philipps Curve; Taylor Rule; Stochastic Differential Equations